2020
DOI: 10.3390/ani10061006
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community and Short-Chain Fatty Acid Mapping in the Intestinal Tract of Quail

Abstract: Quail is raised throughout China for egg and meat production. To deeply understand the gastrointestinal microbial composition and metabolites of quail, the present study characterized the microbiota inhabiting five intestinal locations of eight-week-old quail using 16S rRNA gene sequencing and qPCR, and evaluated the concentrations of short-chain fatty acids (SCFAs) in each individual location using gas chromatography. The results showed that Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria, and Defer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
0
17
0
2
Order By: Relevance
“…It can reduce weight gain, hyperglycemia, and liver steatosis in ob/ob and high-fat diet mice [ 32 ] and significantly reduce the severity of intestinal inflammation in murine models of acute and chronic colitis [ 33 ]. The SCFA-producing Parabacteroides were richer in the cecum and colorectum, where, accordingly, more SCFAs were produced [ 34 ]. Lactococcus lactis activates innate immunity and protects from infections [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can reduce weight gain, hyperglycemia, and liver steatosis in ob/ob and high-fat diet mice [ 32 ] and significantly reduce the severity of intestinal inflammation in murine models of acute and chronic colitis [ 33 ]. The SCFA-producing Parabacteroides were richer in the cecum and colorectum, where, accordingly, more SCFAs were produced [ 34 ]. Lactococcus lactis activates innate immunity and protects from infections [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactococcus lactis activates innate immunity and protects from infections [ 35 , 36 ]. Moreover, some Lactobacilli can produce SCFAs [ 34 ], which can induce Tregs to modulate gut immune responses [ 37 , 38 , 39 ], and can shape the pulmonary immune environment and influence the severity of allergic inflammation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA was extracted from the jejunal and colonic contents of mice using QIAamp DNA Stool Mini Kit (QIAGEN, Valencia, CA, USA). The 16S rRNA gene sequencing and data analysis were performed as described previously (34). Briefly, the V3 and V4 region of bacterial 16S rRNA gene was amplified from each genomic DNA sample by using the barcode-fusion primers 341F and 806R.…”
Section: Dna Extraction and Microbiota Analysismentioning
confidence: 99%
“…The abundances of the major butyrate-producing bacteria, clostridial cluster I, IV, and XIVa and the terminal genes for butyrate synthesis, butyrate kinase (BK) and butyryl CoA: acetate CoA transferase (BCoAT) in mice colon contents were assessed by qPCR on an ABI Prism 7700 detection system (Applied Biosystems, Foster City, CA, USA) using the extracted DNA as templates and SYBR Green PCR Master Mix (Takara, Japan), as previously described (34,37…”
Section: Qpcr Analysis Of Key Bacteria and Genes In Butyrate Productionmentioning
confidence: 99%
“…It has been shown that Lactobacillus culture possess beneficial effects on immune response and cytokines in chickens [17,19]; moreover, it can limit Salmonella colonization [20,21]. Although Lactobacillus is a predominant genus of bacteria normally inhabitant in poultry intestines [22,23]; however, to the best of our knowledge, there is little information available on chicken immune responses to probiotic bacteria, especially when LA is used as a probiotic. Therefore, this study aimed to evaluate the impact of dietary probiotic LA supplementation on cholesterol levels, immune response, and productive performance of laying hens.…”
Section: Introductionmentioning
confidence: 99%